Evolutionary computation for maximizing CO2 and H2 separation in multiple-tube palladium-membrane systems. (1st February 2019) - Chen, Wei-Hsin; Kuo, Pei-Chi; Lin, Yu-Li
Graphical abstract: Highlights: H2 and CO2 separation in multiple membrane tube systems is studied. Membrane system configurations are designed using a two-stage optimization. Parametric sweep technology followed by the Nelder-Mead method adopted used for design. The optimized configuration at Re = 10 can improve the hydrogen recovery up to 12.2%. The CO2 enrichment can be intensified by up to 7%. Abstract: Membrane separation is a promising method to separate CO2 and H2 from hydrogen-rich gases. This simultaneously achieves H2 recovery and CO2 enrichment. The latter is conducive to subsequent carbon capture and storage, and thereby the development of negative emission technologies. In this study, single-, double-, triple-, and quadruple-tube systems with palladium (Pd) membranes and cross-flow configuration are considered, while the Reynolds number ( Re ) is in the range of 1–50. To maximize H2 recovery and CO2 enrichment in the systems, the systems are designed using a two-stage optimization in which the parametric sweep technology followed by the evolutionary computation of the Nelder-Mead simplex method is applied to find the best configuration and the exit H2 concentration is chosen as the objective function. On account of the scavenging waves stemming from the upstream tubes, the goals of the optimization is to diminish the concentration polarization effect of the upstream tubes upon the downstream ones. The predictions indicate that an increase in the number of tubes raises the optimization efficiency. Compared to the tubes in tandem, the optimized configuration at Re = 10 can improve the hydrogen recovery up to 12.2%, while the CO2 enrichment can be intensified by up to 7%.